Brief communication "Does the Eltanin asteroid tsunami provide an alternative explanation for the Australian megatsunami hypothesis?" - D. Dominey-Howes; J. R. Goff (Natural Hazards and Earth System Sciences, 2010)
The Australian megatsunami hypothesis has been developed over two decades. It charts repeated inundation of the South East Australian coast during the Holocene by bolide impact megatsunamis. The most enigmatic evidence for these proposed events are high elevation cliff-top boulders. There is however an absence of known sources for these megatsunamis, and as such we question whether the researchers may have the correct mechanism but the wrong events. Given the low denudation rates of this passive, intraplate environment, we suggest that boulder emplacement may have been solely the result of the much older Eltanin asteroid tsunami about 2.5 Ma ago.